Green internet of things - Mahapatra, Bandana; Nayyar, Anand (Boca Raton, FL : CRC Press, 2023)
"Green Internet of Things envisions the concept of reducing the energy consumption of IoT devices and making the environment safe. Considering this factor, this book focuses on both theoretical and implementation aspects in green computing, next generation networks or networks that can be utilized in providing green systems through IoT enabling technologies, that is, the technology behind its architecture and building components. It also encompasses design concepts and related advanced computing in details. Green Internet of Things : highlights the elements and communication technologies regarding Green Internet of Things, discusses technologies, architecture and components surrounding Green IoT, describes advanced computing technologies in terms of Smart World, Data centres and other related hardware for Green IoT and elaborates energy efficient Green IoT Design for real time implementations, and covers pertinent application in building smart cities, healthcare devices, efficient energy harvesting and so forth. This shortform book is aimed at students, researchers in internet of things, clean technologies, computer science and engineering"--
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things; Electronic apparatus and appliances -- Energy conservation; Green electronics; COMPUTERS / Machine Theory; COMPUTERS / Networking / General; TECHNOLOGY / Electricity